Overweight and obesity in schoolchildren aged 10 to 14 years - Mariana de Lima Mendes Ramos; Elenir Rose Jardim Cury Pontes; Marília de Lima Mendes Ramos; Vivian Rosa dos Santos Paes de Barros (Universidade de Fortaleza, 2014)
Objective: To estimate the prevalence of overweight and obesity in 10- to 14-year-old schoolchildren from both public (state and municipal) and private educational network of Campo Grande-MS, and to verify the association between anthropometric data, physical activity, alimentary habits, sexual maturation and type of school. Methods: The sample was composed of 941 students from public and private school, whose anthropometric data was evaluated by the Body Mass Index and Cole's classification. The body composition was obtained through the body fat percentage and the habits of physical activity were assessed. Dietary habits were raised through questions about frequency of consumption of foods with high caloric density, vegetables, legumes and fruits and the habit of eating while watching television. Results: The study identified 217 (23.1%) overweight or obese schoolchildren and 530 (56.3%) with high percentage of body fat. There was not association with the physical activity and the alimentary habits. Overweight and obesity prevalence was higher among schoolchildren with signs of sexual maturation. The students of private schools presented prevalence 1.5 times higher of overweight and obesity, and 1.3 times higher of excess body fat percentage. Conclusion: There was a prevalence of overweight and obesity of 23.1% and 56.3% had high fat percentage, with higher prevalence of overweight and obesity among those with signs of sexual maturation, without association to physical activity and diet. doi:10.5020/18061230.2013.p223